PENDAMPINGAN ORANGTUA PADA SISWA SEKOLAH DASAR DALAM PEMBELAJARAN DARING - Linda Safitri; ratna (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2021)
Education in life plays a role as a tool that can measure the potential development of students. Parents are responsible for the education of their children. The method in this research was descriptive quantitative method. This method was a method that could be used which was based on data obtained directly and supported by literature studies so that it further strengthened the analysis of research data obtained from the results of the calculation of indicators. This study aimed to analyze parental assistance during distance or online learning, especially for elementary school students. Parental assistance was an activity in order to support and assist children in learning, completing tasks that had been assigned by the teacher so that students felt directed, guided and motivated to take part in learning well. Parental assistance could include facilitating learning, supervising activities and the use of study time, recognizing and overcoming learning difficulties. From the results of the research conducted, the results obtained were the values ​​of Sig. ie 0.200, so it could be seen that the significance> 0.05. Therefore, it could be concluded that receiving H0 or the parental assistance variable came from a normally distributed population. Dealing with parents in assisting learning, especially during the implementation of online learning, there were still many obstacles, ranging from the lack of provision of learning facilities, supervision in learning, use of study time, and handling of children's learning difficulties. Keywords: parental assistance, elementary school students, online learning. References: Alaydrus, A.M., & Sarwono. 2018. Analisis Faktor Keterlambatan Dimulainya Pelaksanaan Proyek Kontruksi pada Model Kontrak Rancang Bangun. Jurnal Konstruksia, 10 (1), 95-116. Bilfaqih, Y., & Qomarudin, M. 2015. Esensi Penyusunan Materi Pembelajaran Daring. Yogyakarta: Deepublish. Dewi, W.A.F. 2020. Dampak Covid-19 terhadap implementasi pembelajaran daring di Sekolah Dasar. Edukatif: Jurnal Ilmu Pendidikan, 2(1), 55–61. Eismawati, E., Koeswanti, H., Radia, E. 2019. Peningkatan hasil belajar matematika melalui model pembelajaran problem based learning (PBL) siswa kelas 4 SD. Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 3(2) 71-78. Huang, C., at al. 2020. Clinical Features of Patients Infected with 2019 Novel Coronavirus in Wuhan, China. The Lancet, 395(10223), 497–506. Lestari, I. 2015. Pengaruh Waktu Belajar dan Minat Belajar terhadap Hasil Belajar Matematika. Jurnal Ilmiah Pendidikan MIPA, 3(2), 115–125. Nuraeni & Syihabuddin, S.A. 2020. Mengatasi Kesulitan Belajar Siswa Dengan Pendekatan Kognitif. Jurnal Belaindika, 1(1), 19 – 20. Pratiwi, E.W. 2020. Dampak Covid-19 Terhadap Kegiatan Pembelajaran Online di Sebuah Perguruan Tinggi Kristen di Indonesia. Perspektif Ilmu Pendidikan, 34(1), 1–8. Priyatno, D. 2012. Belajar Cepat Olah Data Statistik dengan SPSS. Yogyakarta: Andi Yogyakarta. Qomaruddin. Q. 2016. Pentingnya Pendampingan Orang Tua Terhadap Pendidikan Anak. Jurnal Studi Islam Dan Muamalah At-Tahdzib Volume 4(2), 2. Rahmania, S., Wijayanti, R., & Hakim, S.L. 2020. Strategi Orang Tua Dalam Pendampingan Belajar Anak Selama Pandemi Covid-19. Jurnal Kajian Keislaman Multi-Perspektif, 1(1), 99-110. Sadulloh, U. 2010. Pedagogik (ilmu mendidik). Bandung: Alfabeta. Sulastri., Imran., & Firmansyah, A. (2014). Meningkatkan Hasil Belajar Siswa Melalui Strategi Pembelajaran Berbasis Masalah Pada Mata Pelajaran IPS di Kelas V SDN 2 Limbo Makmur Kecamatan Bumi Raya. Jurnal Kreatif Tadulako Online 3(1), 92. Susanto, A. 2012. Perkembangan Anak Usia Dini. Jakarta: Kencana. Syah, M. 2015. Psikologi Pelajar. Jakarta: Rajawali Pers. Tohir, M. 2019. Hasil PISA Indonesia Tahun 2018 Turun Dibanding Tahun 2015. Diperoleh 21 Desember 2020, dari https://matematohir.wordpress.com/2019/12/03/hasil-pisaindonesiatahun-2018-turun-dibanding-tahun-2015/. Wahyudi. 2015. Panduan Pembelajaran Matematika Sekolah Dasar. Surakarta: UNS PRESS. Watimury, P., & Bahalwan, F. 2019. Pengaruh Lingkungan Belajar Dan Konsep Diri Terhadap Hasil Belajar Biologi Siswa SMP Negeri I Maluku Tengah. Jurnal Biology Science & Education, 8(1), 41-46. Yanti, N.K.K., Suarjana, I.M., & Astawan, I.G. Pendampingan Orang Tua Terhadap Hasil Belajar Matematika Dalam Pembelajaran Daring. Jurnal Pedagogi Dan Pembelajaran, 4(2), 1-5. Yulianingsih, W., & Nugroho, R. 2021. Keterlibatan Orangtua dalam Pendampingan Belajar Anak selama Masa Pandemi Covid-19. 5(2), 1138–115.